2012
DOI: 10.1111/opn.12012
|View full text |Cite
|
Sign up to set email alerts
|

Person‐centred care in nursing documentation

Abstract: Aims and objectives To explore nursing documentation in long‐term care, to determine whether it reflected a person‐centred approach to care and to describe aspects of PCC as they appeared in nursing records. Background Documentation is an essential part of nursing. It provides evidence that care has been carried out and contains important information to enhance the quality and continuity of care. Person‐centred care (PCC) is an approach to care that is underpinned by mutual respect and the development of a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 44 publications
4
61
0
6
Order By: Relevance
“…The need to enhance the visualization of a patient's needs, resources, and wishes – instead of nurses’ tasks – in documentation has been emphasized for some time (Kärkkäinen, Bondas, & Eriksson, ). Such documentation was sparse, but in line with previous studies (Broderick & Coffey, ). The review of medical records indicated an increased awareness among healthcare personnel of assessing patients’ resources.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The need to enhance the visualization of a patient's needs, resources, and wishes – instead of nurses’ tasks – in documentation has been emphasized for some time (Kärkkäinen, Bondas, & Eriksson, ). Such documentation was sparse, but in line with previous studies (Broderick & Coffey, ). The review of medical records indicated an increased awareness among healthcare personnel of assessing patients’ resources.…”
Section: Discussionsupporting
confidence: 84%
“…As documentation constitutes a part of the model of initiating, integrating, and securing PCC (Ekman, Swedberg, et al., ), a protocol for reviewing person‐centred content in medical records was developed within the scope of this study. The protocol was based on the dimensions and items in an existing framework for reviewing nursing documentation in the care of elders (Broderick & Coffey, ) and further developed by researchers with expertise in PCC and psychometric analysis. The final protocol for review included 10 items divided between three dimensions (Table ).…”
Section: The Studymentioning
confidence: 99%
“…To effectively provide person‐centred care, caregivers need information about the background and personal interests of the residents. As found in Broderick and Coffey (), this information was not always available, which was a barrier to successful implementation on two wards. However, in addition to developing more effective ways to retrieve this information, the application of the multi‐faceted VCM training and coaching program, including careful observation of the reactions of the residents, provides valuable insight into their personal interests and preferences.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, in LTC, many—perhaps most—staff are not trained in communication approaches that might engage residents in care planning (Børøsund, Ruland, Moore, & Ekstedt, 2014; Savundranayagam, 2014). The structure of nursing documentation—especially the tendency for care planning forms to require limited psychosocial detail—is likewise an obstacle (Broderick & Coffey, 2013). …”
Section: Resultsmentioning
confidence: 99%